ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL DENGAN PENERAPAN MODEL GAME BASED LEARNING PADA MATA PELAJARAN SOSIOLOGI KELAS XII IPS SMA SANTUN UNTAN - Bellestari, Septia; Ramadhan, Iwan; Zatalini, Adhalia (Universitas Tanjungpura, 2025)
This study aims to analyze the use of Wordwall learning media with the application of the Game Based Learning model in Sociology class XII IPS at Santun Untan High School. The implementation of learning in class XII IPS SMA SANTUN took place in accordance with the criteria, namely from the pretest conducted using Wordwall as the initial test, followed by treatment aimed at increasing student engagement and motivation in understanding social inequality material through enjoyable learning, and finally, the posttest showed that students were more familiar with the appearance and workings of the platform because they had actively used it during the treatment. This research uses a quantitative approach with a pseudo-experimental method (pre-experimental design) using a one group pretest-posttest design. The number of subjects in this study were 26 students. Data collection techniques were carried out through tests (pretest and posttest) and observation of student activity during learning. The results showed that the average student pretest score was 30.5 while the average posttest score increased to 71.2. The normality test showed that the data was not normally distributed, so the Wilcoxon Signed Rank Test non-parametric test was used. The test results showed a significance value of 0.001 (